Commissioning of agricultural transformation building and Senator Abiola Ajimobi Ringroad - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Senator Abiola Ajimobi, the Governor of Oyo State Commissions the Agricultural Transformation Building at IITA, Ibadan on 25th May, 2019.